2009
DOI: 10.1152/jn.00186.2009
|View full text |Cite
|
Sign up to set email alerts
|

P2 Receptor–Mediated Signaling in Spherical Bushy Cells of the Mammalian Cochlear Nucleus

Abstract: Milenkovic I, Rinke I, Witte M, Dietz B, Rü bsamen R. P2 receptor-mediated signaling in spherical bushy cells of the mammalian cochlear nucleus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 125 publications
9
36
0
Order By: Relevance
“…Morphological characterization of the recorded neurons was assessed (as previously shown for CN neurons; Milenkovic et al, 2009) by a post hoc labeling of biocytin-filled neurons with Cy2-conjugated streptavidin, according to the protocol described by (Bischofberger et al, 2006). After recording and fixation in 4% paraformaldehyde (PFA; in 0.1 M PBS, pH 7.3), the slices were washed (6 ϫ 5 min with TBS and 6 ϫ 5 min with TBS/0.3% Triton X-100) and incubated with Cy2-conjugated streptavidin (5 g/ml; Jackson ImmunoResearch) 2.5 h at RT.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Morphological characterization of the recorded neurons was assessed (as previously shown for CN neurons; Milenkovic et al, 2009) by a post hoc labeling of biocytin-filled neurons with Cy2-conjugated streptavidin, according to the protocol described by (Bischofberger et al, 2006). After recording and fixation in 4% paraformaldehyde (PFA; in 0.1 M PBS, pH 7.3), the slices were washed (6 ϫ 5 min with TBS and 6 ϫ 5 min with TBS/0.3% Triton X-100) and incubated with Cy2-conjugated streptavidin (5 g/ml; Jackson ImmunoResearch) 2.5 h at RT.…”
Section: Methodsmentioning
confidence: 99%
“…(1) The slices were bulk labeled by incubation in ACSF supplemented with Fura 2 acetoxymethyl ester (10 M Fura-2 AM; Invitrogen) and 0.025% (w/v) pluronic acid, for 30 min at 37°C, as described previously (Milenkovic et al, 2009). (2) Alternatively, the measurement of intracellular calcium was performed simultaneously with whole-cell recordings.…”
Section: Fluorometric Ca 2ϩ Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The P2Y-activated cation nonselective, depolarizing conductance, can reinforce neuronal excitability at the level of the perikaryon and facilitate the propagation of action potentials along the nerve fibers. Interestingly, it has recently been shown that P2Y receptors, cooperating with a simultaneously evoked P2X conductance, increased the neuronal firing rates in the mammalian cochlear nucleus [73]. Moreover, control of intracellular calcium can modify neuronal survival (trophic effect), and the neurons can recognize environmental pathologic events by sensing dispersed ATP via purinergic receptors (damage confrontation), thereby invoking (so far unknown) self-defense intracellular mechanisms.…”
Section: Neuromodulation In Sgn/vgnmentioning
confidence: 99%